Low-odor cold-resistant wear-resistant elastic injection molding material and preparation method thereof
By constructing the composite morphology of cellulose sol coated nanoparticles and melt blending with PVC resin powder, a three-dimensional interlocking structure is formed, which solves the shortcomings of PVC elastic injection molding in terms of bending resistance and dimensional stability, and achieves high performance under low temperature conditions.
Patent Information
- Application Number
- CN202411599104.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PVC elastic injection moldings have shortcomings in bending resistance and dimensional stability, especially in low temperature conditions.
A cellulose sol system is constructed by tetrabutyl ammonium hydroxide and carboxymethyl cellulose, preload and calcium chloride are added, and hot carbon dioxide gas is introduced to form a composite form of cellulose sol-coated nanoparticles. The layered composite material is prepared after impregnation and hot pressing, and melt blended with PVC resin powder to form a three-dimensional interlocking structure to enhance toughness and stability.
It significantly improves the bending and winding resistance and dimensional stability of PVC elastic injection molding, can maintain low shrinkage and good elastic properties under low temperature conditions of -40℃, and is suitable for applications such as electric vehicle parts.
Smart Images

Figure CN119708720A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of elastic injection molding materials, and more specifically, to a low-odor, cold-resistant, and wear-resistant elastic injection molding material and a preparation method thereof. Background Art
[0002] Elastic injection molding materials are mainly used to produce elastic injection molded parts. They are characterized by high elasticity and resistance to stress fatigue and are widely used in the fields of electronic appliances, toys, daily necessities, home decoration, automotive parts, electric vehicle parts, etc. PVC is a widely used thermoplastic polymer among elastic injection molding materials. The injection molding process involves melting PVC resin and injecting it into the mold cavity, and then cooling and solidifying it into the desired shape.
[0003] With the continuous development of new energy technologies, electric vehicles have gradually become the main means of transportation for people. Many parts of electric vehicles need to have good elasticity, comfort and safety. However, flexible parts made of traditional materials such as rubber or plastic have problems such as poor wear resistance, variability, and strong odor. Therefore, PVC elastic injection molding parts as an alternative material can improve elasticity, toughness, low odor and other properties, thereby improving the service life and comfort of related parts.
[0004] For example, the patent application document with application publication number CN117511087A discloses a high-toughness and high-fluidity PVC injection molding material and its preparation method, which includes the following raw materials in parts by weight: 100 parts of PVC, 0.3-2.5 parts of internal lubricant, 0.1-1.5 parts of external lubricant, 1-6 parts of stabilizer, 8-15 parts of toughening modifier, 0-6 parts of plasticizer, 0-3 parts of ACR processing aid, and 0-15 parts of nano calcium carbonate; the toughening modifier includes a first raw material and a second raw material, the first raw material includes a first toughening agent, a second toughening agent and nanoparticles, the first toughening agent includes one or more of CPE, EVA, and nitrile rubber, the second toughening agent includes one or more of MBS, ABS high-rubber powder, and ACR, and the second raw material includes zinc stearate. It improves the problems of low notched impact strength, poor low-temperature toughness, and poor processing fluidity of PVC products.
[0005] In the above documents, although the toughness of PVC is improved, the shrinkage rate is large and the dimensional stability is still poor, which brings inconvenience to subsequent assembly and use; and many parts of electric vehicles need to have better bending resistance, which are problems that urgently need to be improved in existing PVC injection molding materials. Summary of the invention
[0006] In order to further improve the bending resistance and dimensional stability of PVC elastic injection molding materials, the present application provides a low-odor, cold-resistant, and wear-resistant elastic injection molding material and a preparation method thereof.
[0007] In a first aspect, the present application provides a method for preparing a low-odor, cold-resistant, and wear-resistant elastic injection molding material, using the following technical solution: A method for preparing a low-odor, cold-resistant, and wear-resistant elastic injection molding material, characterized in that it comprises the following steps: 1) 80-120 parts of PVC resin powder, 65-80 parts of diisodecyl phthalate, 4.5-5.5 parts of stabilizer, 4-6 parts of calcium powder, and 0.3-0.5 parts of lubricant are mixed, kneaded, and dried, and then 10-15 parts of diisodecyl phthalate are added to continue mixing to obtain a mixture; 2) Take 20-35 parts of carrageenan, 5-10 parts of vegetable protein, and 100-150 parts of water and stir them evenly, add dimethyl sulfoxide and urea and continue to stir evenly, dry and calcine, grind and obtain the pre-material; 3) Add tetrabutylammonium hydroxide solution and carboxymethyl cellulose into the container, mix well, add pre-material and calcium chloride, add ethanol and triethanolamine under continuous stirring, and then introduce excess hot carbon dioxide gas into the container. After the ethanol and triethanolamine are completely removed, evacuate the container, and then scrape the film on a scraping board, and then put it into water for setting and washing to obtain a film material; 4) taking the film material and soaking it in an impregnation liquid, and then hot pressing and drying it, and crushing it to obtain a layered composite material; the impregnation liquid includes water, sodium polystyrene sulfonate and hydroxyproline; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.1-0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
[0008] Preferably, the step 2) further includes one or more of the following technical features: 21) The plant protein is at least one of soy protein, wheat protein and corn protein; 22) The calcination treatment is performed at a temperature of 700-850°C; 23) The amount of dimethyl sulfoxide added is 5-10% of the mass of carrageenan, and the amount of urea added is 3-5% of the mass of carrageenan.
[0009] Preferably, the step 3) further includes at least one of the following technical features: 31) The volume mass ratio of the tetrabutylammonium hydroxide solution, carboxymethyl cellulose, pre-material and calcium chloride is 100-150mL:20-40g:10-15g:3-5g; 32) The temperature of the carbon dioxide gas is 75-90°C.
[0010] Preferably, the step 4) further includes at least one of the following technical features: 41) The mass ratio of water, sodium polystyrene sulfonate and hydroxyproline in the impregnation solution is 1:0.15-0.2:0.05-0.075; 42) The immersion time is 20-35 minutes; 43) The hot pressing temperature is 120-150°C.
[0011] Preferably, the step 5) further includes at least one of the following technical features: 51) The processing temperature of twin-screw extruder is: zone 1 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃; 52) The processing temperature of single screw extruder is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃; 53) The die temperature is 130℃±5℃.
[0012] Preferably, the average particle size of the pre-material is 50-300 μm.
[0013] Preferably, the degree of polymerization of the PVC resin powder is greater than 1000.
[0014] In a second aspect, the present application provides a low-odor, cold-resistant, and wear-resistant elastic injection molding material, which is prepared by the above-mentioned preparation method.
[0015] Preferably, the tensile strength of the low-odor, cold-resistant, and wear-resistant elastic injection molding material is greater than 12.5 MPa.
[0016] Preferably, the shrinkage rate of the low-odor, cold-resistant, and wear-resistant elastic injection molding material is less than 2%.
[0017] In summary, this application has the following beneficial effects: 1. The present application uses tetrabutylammonium hydroxide and carboxymethyl cellulose to construct a cellulose sol system, and then adds pre-materials and calcium chloride. After hot carbon dioxide gas is introduced, a cellulose sol-coated nanoparticle composite form is formed. After impregnation and hot pressing, a layered composite material with high strength and high toughness is obtained. After the layered composite material and PVC resin powder are melt-blended, the layered composite material is evenly dispersed in the resin system, and its own layered structure is used to form a three-dimensional interlocking. The pull-out mechanism generated by the layered structure in the polymer resin system greatly dissipates the stress of the injection molding material, which plays a good toughening and strengthening role. And this interlocking and pull-out effect can greatly reduce the shrinkage rate of injection molded parts and improve dimensional stability.
[0018] 2. This application uses carrageenan and plant protein as template materials, and then adds dimethyl sulfoxide and urea. After calcination, a biochar material is formed. The prepared biochar material has a large number of sulfur vacancies and nitrogen vacancies, forming a porous structure with a large specific surface area and strong interface interaction. The synergistic effect of micro-nanoscale particles is used to improve the compatibility of the layered composite material with the resin system, and also improve the low-temperature impact resistance of the injection molded parts.
[0019] 3. The low-odor, cold-resistant, wear-resistant elastic injection molding material prepared by the preparation method of the present application can simultaneously meet the harsh conditions of low odor and low temperature of -40°C, and can meet the requirements of shrinkage less than 2%, and can be quickly and adaptively embedded in the mold to achieve the expected use and assembly effect. In addition, in the selection of plasticizers, the plasticizer of diisodecyl phthalate is mainly selected, and toluene or benzene is not selected. The main advantage of this plasticizer is that the odor released at high and low temperatures is extremely low, and basically no irritating odor can be smelled. In addition, the present application has achieved a hardness of 80P in hardness. At this hardness, it can meet the low temperature of -40°C, and it is also very elastic and easy to embed in the mold. It can meet more than 5 million bending and winding with high polymerization degree resin powder and layered composite materials. In addition, the density of the low-odor, cold-resistant, wear-resistant elastic injection molding material of the present application is very low, and the inorganic filler is added very little, which is helpful to low temperature and elasticity to a certain extent, and can play a certain shaping and role to prevent material bridging. At the same time, it can also improve the dimensional stability when the material is inlaid or assembled after demoulding, and prevent the material from shrinking too much or too little, which may make it difficult to inlay or assemble successfully. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the shrinkage performance test of the low-odor, cold-resistant, and wear-resistant elastic injection molding materials of Examples 1-3 and Comparative Examples 1-5 of the present application.
[0021] Figure 2 is a cross-sectional SEM image of the layered composite material prepared in Example 3 of the present application. DETAILED DESCRIPTION
[0022] The present application provides a method for preparing a low-odor, cold-resistant, and wear-resistant elastic injection molding material, comprising the following steps: 1) 80-120 parts of PVC resin powder, 65-80 parts of diisodecyl phthalate, 4.5-5.5 parts of stabilizer, 4-6 parts of calcium powder, and 0.3-0.5 parts of lubricant are mixed, kneaded, and dried, and then 10-15 parts of diisodecyl phthalate are added to continue mixing to obtain a mixture; 2) Take 20-35 parts of carrageenan, 5-10 parts of vegetable protein, and 100-150 parts of water and stir them evenly, add dimethyl sulfoxide and urea and continue to stir evenly, dry and calcine, grind and obtain the pre-material; 3) Add tetrabutylammonium hydroxide solution and carboxymethyl cellulose into the container, mix well, add pre-material and calcium chloride, add ethanol and triethanolamine under continuous stirring, and then introduce excess hot carbon dioxide gas into the container. After the ethanol and triethanolamine are completely removed, evacuate the container, and then scrape the film on a scraping board, and then put it into water for setting and washing to obtain a film material; 4) taking the film material and soaking it in an impregnation liquid, and then hot pressing and drying it, and crushing it to obtain a layered composite material; the impregnation liquid includes water, sodium polystyrene sulfonate and hydroxyproline; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.1-0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
[0023] In step 2) of the method for preparing the low-odor, cold-resistant, and wear-resistant elastic injection molding material of the present application, the calcination treatment is calcined at a temperature of 700-850° C. In some specific embodiments, the calcination treatment is calcined at a temperature of 700° C., 750° C., 800° C., or 850° C.
[0024] In some specific embodiments, in step 2), the amount of dimethyl ether added is 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10% of the mass of carrageenan. The amount of urea added is 3%, 3.5%, 4%, 4.5%, 5% of the mass of carrageenan.
[0025] In some specific embodiments, in step 3), the volume mass ratio of tetrabutylammonium hydroxide solution, carboxymethyl cellulose, pre-material and calcium chloride can be 100mL:20g:10g:3g, 150mL:40g:15g:5g, 100mL:20g:10g:3g, 100mL:40g:10g:5g, 150mL:20g:15g:3g, 120mL:30g:12g:3.5g, 120mL:40g:15g:5g, 150mL:20g:15g:5g, 150mL:40g:10g:3g, 150mL:40g:10g:5g.
[0026] Optionally, in some embodiments, the temperature of the carbon dioxide gas may be 75°C, 80°C, 85°C, or 90°C.
[0027] Optionally, in some specific embodiments, the mass ratio of water, sodium polystyrene sulfonate and hydroxyproline in the impregnation solution is 1:0.15:0.05, 1:0.2:0.075, 1:0.15:0.075, 1:0.2:0.05, 1:0.18:0.05, 1:0.18:0.075, 1:0.18:0.065, 1:0.15:0.065, 1:0.15:0.05.
[0028] In some specific embodiments, in step 4), the immersion time is 20 min, 25 min, 30 min, or 35 min.
[0029] In some specific embodiments, in step 4), the hot pressing temperature is 120°C, 130°C, 140°C, or 150°C.
[0030] Optionally, in some specific embodiments, the average particle size of the precursor may be 50 μm, 100 μm, 150 μm, 200 μm, 250 μm, or 300 μm.
[0031] Optionally, in some specific embodiments, the degree of polymerization of the PVC resin powder may be 1100, 1200, 1300, or 1500.
[0032] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0033] The present application is further described in detail below with reference to the embodiments. Example 1
[0034] The method for preparing the low-odor, cold-resistant, and wear-resistant elastic injection molding material of this embodiment comprises the following steps: 1) 10 kg of PVC resin powder, 6.5 kg of diisodecyl phthalate, 0.5 kg of stabilizer, 0.5 kg of calcium powder and 0.03 kg of lubricant were mixed, kneaded and dried, and then 1.5 kg of diisodecyl phthalate was added to continue mixing to obtain a mixture; 2) Take 2kg of carrageenan, 1kg of vegetable protein, and 10kg of water and stir evenly, add 0.1kg of dimethyl sulfoxide and 0.1kg of urea and continue stirring evenly, dry and calcine at 700°C, grind and obtain the pre-material, the average particle size of the pre-material is 300μm; 3) Add 150 mL of 40% tetrabutylammonium hydroxide solution and 40 g of carboxymethyl cellulose into the container, mix well, add 10 g of pre-material and 5 g of calcium chloride, add 50 mL of ethanol and 30 mL of triethanolamine under constant stirring, then introduce excess carbon dioxide gas at 90 ° C into the container, heat to remove ethanol and triethanolamine, and after the ethanol and triethanolamine are completely removed, evacuate, and then scrape the film on a scraping plate with a film thickness of 1.5 mm, then put it into water for shaping and washing to obtain a film material; 4) taking the film material and soaking it in the impregnation liquid, and then hot pressing and drying it, and crushing it to obtain a layered composite material; the mass ratio of water, sodium polystyrene sulfonate and hydroxyproline in the impregnation liquid is 1:0.15:0.075; the hot pressing temperature is 150°C, and the impregnation time is 20 minutes; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
[0035] Among them, the model of PVC resin powder is PVC-SG-3, and the degree of polymerization is 1300. The stabilizer is stabilizer K7004. The lubricant is composed of PE wax and stearic acid in a mass ratio of 1:1. The calcium powder is nano calcium carbonate, and the particle size distribution range is 20-50nm. The plant protein is soy protein. The processing temperature of twin-screw extrusion is: zone 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃. The processing temperature of single-screw extrusion is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃. The die head temperature is 130℃±5℃. Example 2
[0036] The method for preparing the low-odor, cold-resistant, and wear-resistant elastic injection molding material of this embodiment comprises the following steps: 1) 10 kg of PVC resin powder, 6.5 kg of diisodecyl phthalate, 0.5 kg of stabilizer, 0.5 kg of calcium powder and 0.03 kg of lubricant were mixed, kneaded and dried, and then 1.5 kg of diisodecyl phthalate was added to continue mixing to obtain a mixture; 2) Take 3.5kg carrageenan, 0.5kg vegetable protein, and 15kg water and stir evenly, add 0.35kg dimethyl sulfoxide and 0.0525kg urea and continue stirring evenly, dry and calcine at 850°C, grind and obtain the pre-material, the average particle size of the pre-material is 50μm; 3) Add 100 mL of 40% tetrabutylammonium hydroxide solution and 20 g of carboxymethyl cellulose into the container, mix well, add 15 g of pre-material and 3 g of calcium chloride, add 50 mL of ethanol and 30 mL of triethanolamine under constant stirring, then introduce excess carbon dioxide gas at a temperature of 75 ° C into the container, heat to remove ethanol and triethanolamine, and after the ethanol and triethanolamine are completely removed, evacuate, and then scrape the film on a scraping plate with a film thickness of 1.5 mm, then put it into water for shaping and washing to obtain a film material; 4) The film material is immersed in an impregnation liquid, and then hot-pressed, dried, and crushed to obtain a layered composite material; the mass ratio of water, sodium polystyrene sulfonate, and hydroxyproline in the impregnation liquid is 1:0.2:0.05; the hot-pressing temperature is 120°C, and the impregnation time is 35 minutes; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.1 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
[0037] Among them, the model of PVC resin powder is PVC-SG-3, and the degree of polymerization is 1300. The stabilizer is stabilizer K7004. The lubricant is composed of PE wax and stearic acid in a mass ratio of 1:1. The calcium powder is nano calcium carbonate, and the particle size distribution range is 20-50nm. The plant protein is soy protein. The processing temperature of twin-screw extrusion is: zone 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃. The processing temperature of single-screw extrusion is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃. The die head temperature is 130℃±5℃. Example 3
[0038] The method for preparing the low-odor, cold-resistant, and wear-resistant elastic injection molding material of this embodiment comprises the following steps: 1) 10 kg of PVC resin powder, 6.5 kg of diisodecyl phthalate, 0.5 kg of stabilizer, 0.5 kg of calcium powder and 0.03 kg of lubricant were mixed, kneaded and dried, and then 1.5 kg of diisodecyl phthalate was added to continue mixing to obtain a mixture; 2) Take 3kg of carrageenan, 0.8kg of vegetable protein, and 15kg of water and stir evenly, add 0.3kg of dimethyl sulfoxide and 0.15kg of urea and continue to stir evenly, dry and calcine at 750°C, grind and obtain the pre-material, the average particle size of the pre-material is 150μm; 3) Add 120mL of 40% tetrabutylammonium hydroxide solution and 30g of carboxymethyl cellulose into the container, mix well, add 12g of pre-material and 5g of calcium chloride, add 50mL of ethanol and 30mL of triethanolamine under constant stirring, then introduce excess carbon dioxide gas at a temperature of 85°C into the container, heat to remove ethanol and triethanolamine, and after the ethanol and triethanolamine are completely removed, evacuate, and then scrape the film on a scraping plate with a film thickness of 1.5mm, then put it into water for shaping and washing to obtain a film material; 4) The film material is immersed in an impregnation liquid, and then hot-pressed, dried, and crushed to obtain a layered composite material; the mass ratio of water, sodium polystyrene sulfonate, and hydroxyproline in the impregnation liquid is 1:0.2:0.05; the hot-pressing temperature is 130°C, and the impregnation time is 25 minutes; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.15 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
[0039] Among them, the model of PVC resin powder is PVC-SG-3, and the degree of polymerization is 1300. The stabilizer is stabilizer K7004. The lubricant is composed of PE wax and stearic acid in a mass ratio of 1:1. The calcium powder is nano calcium carbonate, and the particle size distribution range is 20-50nm. The plant protein is soy protein. The processing temperature of twin-screw extrusion is: zone 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃. The processing temperature of single-screw extrusion is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃. The die head temperature is 130℃±5℃.
[0040] Comparative Example 1 The preparation method of the low-odor, cold-resistant, and wear-resistant elastic injection molding material of this comparative example is different from that of Example 1 in that an equal amount of dioctyl terephthalate is used to replace diisodecyl phthalate, which is the same as that in Example 1.
[0041] Comparative Example 2 The preparation method of the low-odor, cold-resistant, and wear-resistant elastic injection molding material of this comparative example is different from that of Example 1 in that the amount of diisodecyl phthalate added to the raw material is adjusted from 8 kg to 6.5 kg, which is the same as that in Example 1.
[0042] Comparative Example 3 The preparation method of the low-odor cold-resistant and wear-resistant elastic injection molding material of this comparative example comprises the following steps: 1) 10 kg of PVC resin powder, 6.5 kg of diisodecyl phthalate, 0.5 kg of stabilizer, 0.5 kg of calcium powder and 0.03 kg of lubricant were mixed, kneaded and dried, and then 1.5 kg of diisodecyl phthalate was added to continue mixing to obtain a mixture; 2) Add 150 mL of 40% tetrabutylammonium hydroxide solution and 40 g of carboxymethyl cellulose into the container, mix well and add 5 g of calcium chloride, add 50 mL of ethanol and 30 mL of triethanolamine under constant stirring, then introduce excess carbon dioxide gas at 90 ° C into the container, heat to remove ethanol and triethanolamine, and after the ethanol and triethanolamine are completely removed, evacuate the container, and then scrape the film on a scraping board with a film thickness of 1.5 mm, then put it into water for shaping and washing to obtain a film material; 3) The film material is immersed in an impregnation liquid, and then hot-pressed, dried, and crushed to obtain a layered composite material; the mass ratio of water, sodium polystyrene sulfonate, and hydroxyproline in the impregnation liquid is 1:0.15:0.075; the hot-pressing temperature is 150°C, and the impregnation time is 20 minutes; 4) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding material is obtained.
[0043] Among them, the model of PVC resin powder is PVC-SG-3, and the degree of polymerization is 1300. The stabilizer is stabilizer K7004. The lubricant is composed of PE wax and stearic acid in a mass ratio of 1:1. The calcium powder is nano calcium carbonate, and the particle size distribution range is 20-50nm. The processing temperature of twin-screw extrusion is: zone 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃. The processing temperature of single-screw extrusion is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃. The die head temperature is 130℃±5℃.
[0044] Comparative Example 4 The preparation method of the low-odor cold-resistant and wear-resistant elastic injection molding material of this comparative example comprises the following steps: 1) 10 kg of PVC resin powder, 6.5 kg of diisodecyl phthalate, 0.5 kg of stabilizer, 0.5 kg of calcium powder and 0.03 kg of lubricant were mixed, kneaded and dried, and then 1.5 kg of diisodecyl phthalate was added to continue mixing to obtain a mixture; 2) Take 2kg of carrageenan, 1kg of vegetable protein, and 10kg of water and stir evenly, add 0.1kg of dimethyl sulfoxide and 0.1kg of urea and continue stirring evenly, dry and calcine at 700°C, grind and obtain the pre-material, the average particle size of the pre-material is 300μm; 3) The mixed material and the pre-processed material are mixed in a mass ratio of 1:0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding material is obtained.
[0045] Among them, the model of PVC resin powder is PVC-SG-3, and the degree of polymerization is 1300. The stabilizer is stabilizer K7004. The lubricant is composed of PE wax and stearic acid in a mass ratio of 1:1. The calcium powder is nano calcium carbonate, and the particle size distribution range is 20-50nm. The plant protein is soy protein. The processing temperature of twin-screw extrusion is: zone 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃. The processing temperature of single-screw extrusion is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃. The die head temperature is 130℃±5℃.
[0046] Comparative Example 5 The preparation method of the low-odor cold-resistant and wear-resistant elastic injection molding material of this comparative example comprises the following steps: 1) 10 kg of PVC resin powder, 6.5 kg of diisodecyl phthalate, 0.5 kg of stabilizer, 0.5 kg of calcium powder and 0.03 kg of lubricant were mixed, kneaded and dried, and then 1.5 kg of diisodecyl phthalate was added to continue mixing to obtain a mixture; 2) Take 2kg of carrageenan, 1kg of vegetable protein, and 10kg of water and stir evenly, add 0.1kg of dimethyl sulfoxide and 0.1kg of urea and continue stirring evenly, dry and calcine at 700°C, grind and obtain the pre-material, the average particle size of the pre-material is 300μm; 3) Add 150 mL of 40% tetrabutylammonium hydroxide solution and 40 g of carboxymethyl cellulose into the container, mix well, add 10 g of pre-material and 5 g of calcium chloride, add 50 mL of ethanol and 30 mL of triethanolamine under constant stirring, then introduce excess carbon dioxide gas at 90 ° C into the container, heat to remove ethanol and triethanolamine, and after the ethanol and triethanolamine are completely removed, evacuate, and then scrape the film on a scraping plate with a film thickness of 1.5 mm, then put it into water for shaping and washing to obtain a film material; 4) The film material is hot-pressed, dried, and crushed to obtain a layered composite material; the hot-pressing temperature is 150°C; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
[0047] Among them, the model of PVC resin powder is PVC-SG-3, and the degree of polymerization is 1300. The stabilizer is stabilizer K7004. The lubricant is composed of PE wax and stearic acid in a mass ratio of 1:1. The calcium powder is nano calcium carbonate, and the particle size distribution range is 20-50nm. The plant protein is soy protein. The processing temperature of twin-screw extrusion is: zone 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃. The processing temperature of single-screw extrusion is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃. The die head temperature is 130℃±5℃.
[0048] Performance testing The low-odor, cold-resistant, and wear-resistant elastic injection molding materials of Examples 1-3 and Comparative Examples 1-5 were tested for performance, and Example 3 with better test data was taken as a typical sample. The test results are shown in Table 1.
[0049] Table 1 The shrinkage performance test of the low-odor, cold-resistant, and wear-resistant elastic injection molding materials of Examples 1-3 and Comparative Examples 1-5 was analyzed separately, and the results were as follows: Figure 1 shown.
[0050] The cross-sectional SEM test of the layered composite material prepared in Example 3 was performed, and the results were as follows: Figure 2 shown.
[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material, characterized in that: The steps include: 1) 80-120 parts of PVC resin powder, 65-80 parts of diisodecyl phthalate, 4.5-5.5 parts of stabilizer, 4-6 parts of calcium powder, and 0.3-0.5 parts of lubricant are mixed, kneaded, and dried, and then 10-15 parts of diisodecyl phthalate are added to continue mixing to obtain a mixture; 2) Take 20-35 parts of carrageenan, 5-10 parts of vegetable protein, and 100-150 parts of water and stir them evenly, add dimethyl sulfoxide and urea and continue to stir evenly, dry and calcine, grind and obtain the pre-material; 3) Add tetrabutylammonium hydroxide solution and carboxymethyl cellulose into the container, mix well, add pre-material and calcium chloride, add ethanol and triethanolamine under continuous stirring, and then introduce excess hot carbon dioxide gas into the container. After the ethanol and triethanolamine are completely removed, evacuate the container, and then scrape the film on a scraping board, and then put it into water for setting and washing to obtain a film material; 4) taking the film material and soaking it in an impregnation liquid, and then hot pressing and drying it, and crushing it to obtain a layered composite material; the impregnation liquid includes water, sodium polystyrene sulfonate and hydroxyproline; 5) The mixed material and the layered composite material are mixed in a mass ratio of 1:0.1-0.2 and passed through a twin-screw extruder, a single-screw extruder, and a die head in sequence, and then pelletized, air-cooled, and conveyed. After screening, a low-odor, cold-resistant, and wear-resistant elastic injection molding compound is obtained.
2. The method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The step 2) also includes one or more of the following technical features: 21) The plant protein is at least one of soy protein, wheat protein and corn protein; 22) The calcination treatment is performed at a temperature of 700-850°C; 23) The amount of dimethyl sulfoxide added is 5-10% of the mass of carrageenan, and the amount of urea added is 3-5% of the mass of carrageenan.
3. The method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The step 3) further includes at least one of the following technical features: 31) The volume mass ratio of the tetrabutylammonium hydroxide solution, carboxymethyl cellulose, pre-material and calcium chloride is 100-150mL:20-40g:10-15g:3-5g; 32) The temperature of the carbon dioxide gas is 75-90°C.
4. The method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The step 4) further includes at least one of the following technical features: 41) The mass ratio of water, sodium polystyrene sulfonate and hydroxyproline in the impregnation solution is 1:0.15-0.2:0.05-0.075; 42) The immersion time is 20-35 minutes; 43) The hot pressing temperature is 120-150°C.
5. The method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The step 5) further includes at least one of the following technical features: 51) The processing temperature of twin-screw extruder is: zone 1 110℃±5℃, zone 2 120℃±5℃, zone 3 120℃±5℃, zone 4 125℃±5℃, zone 5 125℃±5℃, zone 6 120℃±5℃, zone 7 115℃±5℃, zone 8 100℃±5℃, zone 9 90℃±5℃; 52) The processing temperature of single screw extruder is: zone 1 105±5℃, zone 2 110±5℃, zone 3 120±5℃; 53) The die temperature is 130℃±5℃.
6. The method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The average particle size of the pre-material is 50-300 μm.
7. The method for preparing a low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The polymerization degree of the PVC resin powder is greater than 1000.
8. A low-odor, cold-resistant, and wear-resistant elastic injection molding material, prepared by the preparation method according to any one of claims 1 to 7.
9. The low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The low-odor, cold-resistant, and wear-resistant elastic injection molding material has a tensile strength greater than 12.5 MPa.
10. The low-odor, cold-resistant, wear-resistant elastic injection molding material according to claim 1, characterized in that: The shrinkage rate of the low-odor, cold-resistant, and wear-resistant elastic injection molding material is less than 2%.
Citation Information
Patent Citations
High-toughness and high-fluidity PVC injection molding material and preparation method thereof
CN117511087A
High-temperature-resistant, low-shrinkage, oil-proof and flame retardant polyvinyl chloride cable material and preparation method thereof
CN104194230A
Method for preparing hollow nano calcium carbonate by utilizing ultrasonic aerosol
CN111017973A